Pemanfaatan Larva Magot Dalam Penyusunan Ransum Pakan Puyuh Petelur Di Desa Amadanom Kecamatan Dampit Kabupaten Malang - Suroto, Karunia Setyowati; Djoko, Riyanto (Jurnal Ilmiah Fillia Cendekia, 2024)
Quail farming is a promising micro business with affordable start-up capital and small land area. Quail eggs have high health value and culinary potential. Quail meat is nutritious, their droppings can be used as fertilizer, and their feathers can be made into crafts. Quail can produce up to 300 eggs per year. However, the COVID-19 pandemic and rising feed prices have made it difficult for many farmers. Maggot larvae from the black soldier fly are an economical feed alternative. This study aims to utilize maggot larvae as an economical feed source for laying quail. This research is entitled "Utilization of Maggot Larvae in the Preparation of Feed Ration for Laying Quail in Amadanom Village, Malang District." The focus of the research was to determine the optimal amount of maggot larvae as a partial replacement for manufactured feed and to evaluate the performance of laying quail receiving alternative feed. The results showed that maggot larvae have a high protein and fat content. Partial replacement of manufactured feed with maggot larvae did not affect feed consumption, egg production or daily productivity of laying quails. This indicates that maggot larvae can be an economical source of feed without compromising production. These results support the use of maggot larvae as an alternative to cope with rising feed prices and improve production efficiency of laying quail. This research provides an economical solution to maintain the layer quail farming business amidst the existing economic challenges.